2006
DOI: 10.2174/157340606776056133
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin is an Inhibitor of p300 Histone Acetylatransferase

Abstract: Histone acetyltransferases (HATs), and p300/CBP in particular, have been implicated in cancer cell growth and survival, and as such, HATs represent novel, therapeutically relevant molecular targets for drug development. In this study, we demonstrate that the small molecule natural product curcumin, whose medicinal properties have long been recognized in India and Southeast Asia, is a selective HAT inhibitor. Furthermore the data indicate that alpha, beta unsaturated carbonyl groups in the curcumin side chain f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
69
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 267 publications
(69 citation statements)
references
References 0 publications
0
69
0
Order By: Relevance
“…Curcumin also has been reported to alter HDAC2 expression by chemically preventing its degradation in human monocytes [67]. The α, β-unsaturated carbonyl groups in the side-chain of curcumin are considered to be structurally important for its HAT inhibitory activity [68]. Curcumin also was found to promote proteasomal degradation of p300 and related HATs in prostate cancer cells and peripheral blood lymphocytes [68].…”
Section: Dietary Phytochemicals and Their Epigenetic Modulatory Acmentioning
confidence: 99%
See 1 more Smart Citation
“…Curcumin also has been reported to alter HDAC2 expression by chemically preventing its degradation in human monocytes [67]. The α, β-unsaturated carbonyl groups in the side-chain of curcumin are considered to be structurally important for its HAT inhibitory activity [68]. Curcumin also was found to promote proteasomal degradation of p300 and related HATs in prostate cancer cells and peripheral blood lymphocytes [68].…”
Section: Dietary Phytochemicals and Their Epigenetic Modulatory Acmentioning
confidence: 99%
“…The α, β-unsaturated carbonyl groups in the side-chain of curcumin are considered to be structurally important for its HAT inhibitory activity [68]. Curcumin also was found to promote proteasomal degradation of p300 and related HATs in prostate cancer cells and peripheral blood lymphocytes [68]. Recently, curcumin was found to reduce the acetylation of histone H3 in the IL-6 promoter leading to its decreased expression in rheumatoid arthritis synovial fibroblasts [69].…”
Section: Dietary Phytochemicals and Their Epigenetic Modulatory Acmentioning
confidence: 99%
“…Inhibitors of HDAC enzymes (HDACis) have shown anticancer potential and already entered the clinic (SAHA, vorinostat, Zolinza have been approved for the treatment of advanced cutaneous T-cell lymphoma, CTCL). [9,18,19] Figure 1 depicts selected HAT modulators of different structural classes including the bi-substrate competitors H3-CoA-201 and construct 2, [20][21][22] simple molecules such as MC1626 4, [23] 5 [24] and MB-3 3 [25] and also the natural products curcumin 6, [26,27] garcinol 9 [28] (and its derivative LTK-14 10 [29] ) and anacardic acid (AA) 7.…”
Section: Introductionmentioning
confidence: 99%
“…13 NIH3T3 cells were treated with or without sodium acetate (10 mM) and 1-deoxy-Ac 3 GlcNAlk (200 μM) for 6 h. In-gel fluorescence showed that sodium acetate was able to compete 1-deoxy-GlcNAlk labeling (Figure 2B). To investigate whether any observed protein acetylation by 1-deoxy-GlcNAlk is enzymatic in nature, NIH3T3 cells were pretreated with curcumin (60 μM) for 30 min prior to treatment with 1-deoxy-Ac 3 GlcNAlk (200 μM) for 5.5 h. Cell lysates were then subjected to CuAAC with az-rho and analyzed by in-gel fluorescence scanning (Figure 2C).…”
mentioning
confidence: 99%
“…Likewise, treatment with curcumin resulted in dramatic reduction of the labeling of proteins at low molecular weights but less-so for other proteins. Since curcumin is a specific inhibitor of the p300 acetyltransferase, 13 the proteins that show no change in labeling intensity might be modified by other acetyltransferases. We next directly compared 1-deoxy-GlcNAlk with pentynoic acid.…”
mentioning
confidence: 99%